The ultimate objective of Islamic political actors: a conceptual analysis based on selected hadith - Mohd Syakir Mohd Rosdi,; Kamarul Ariffin Ithnan, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This research was performed in order to study the ultimate objective of Islamic political actors based on selected Hadith of the Prophet. The true ultimate objective from the perspective of Islam should be examined due to the advent of various intentions in politics. Some desired winning in elections. Some desired popularity, while others desired many followers. These desires formed goals that were inconsistent with the ultimate objective of Islamic political actors in the perspective of Islam. The question is, what is this ultimate objective? This study was carried out using the method of literature review and content analysis. Literature review was used in order to collect secondary data, while mawdu‘iy analysis was used in order to analyse those data. As a result, it was found that the ultimate objective of Muslim political actors is to achieve mardhat Allah (the pleasure of Allah).